PERFORMANCE MEASURES FOR ACADEMIC DEPARTMENTS - Al-Turki, Umar (2020)
Measuring the performance of academic departments received little attention compared to other industries due to their complex nature and difficulty to measure their outputs. However, measures of performance are needed to asses whether they meet their set objectives and foster an environment of continuous improvement. The objective of this paper is to develop a performance measurement system for educational institutions. It outlines the properties of adequate performance measures and the steps for developing such measures in educational environment. Inputs and outputs for academic departments are considered as well as processes.